Outcomes of sudden cardiac arrest in a state-wide integrated resuscitation program: Results from the Minnesota Resuscitation Consortium. (January 2017) - Adabag, Selcuk; Hodgson, Lucinda; Garcia, Santiago; Anand, Vidhu; Frascone, Ralph; Conterato, Marc; Lick, Charles; Wesley, Keith; Mahoney, Brian; Yannopoulos, Demetris
Abstract: Background: Despite many advances in resuscitation science the outcomes of sudden cardiac arrest (SCA) remain poor. The Minnesota Resuscitation Consortium (MRC) is a statewide integrated resuscitation program, established in 2011, to provide standardized, evidence-based resuscitation and post-resuscitation care. The objective of this study is to assess the outcomes of a state-wide integrated resuscitation program. Methods: We examined the trends in resuscitation metrics and outcomes in Minnesota since 2011 and compared these to the results from the national Cardiac Arrest Registry to Enhance Survival (CARES) program. Since 2011 MRC has expanded significantly providing service to >75% of Minnesota's population. Results: A total of 5192 SCA occurred in counties covered by MRC from 2011 to 2014. In this period, bystander cardiopulmonary resuscitation (CPR) and use of hypothermia, automatic CPR device and impedance threshold device increased significantly (p < 0.0001 for all). Compared to CARES, SCA cases in Minnesota were more likely to be ventricular fibrillation (31% vs. 23%, p < 0.0001) but less likely to receive bystander CPR (33% vs. 39%, p < 0.0001). Survival to hospital discharge with good or moderate cerebral performance (12% vs. 8%, p < 0.0001), survival in SCA with a shockable rhythm (Utstein survival) (38% vs. 33%, p = 0.0003) and Utstein survival with bystander CPR (44% vs. 37%, p = 0.003) were greater in Minnesota than CARES. Conclusions: State-wide integration of resuscitation services in Minnesota was feasible. Survival rate after cardiac arrest is greater in Minnesota compared to the mean survival rate in CARES.